Thermal Stability Improvement of Sb2Te Material with Rapid Phase Transition. (7th November 2014) - Meng, Yun; Ji, Xinglong; Han, Peigao; Song, Zhitang; Zhou, Wangyang; Guo, Wenjing; Qian, Bo; Wu, Liangcai
Abstract : In this paper, phase change characteristics of SiO2 -doped Sb2 Te materials were systematically investigated. It was found that phase change properties of Sb2 Te were remarkably improved through SiO2 addition. The crystallization temperature is enhanced obviously, showing a relatively good thermal stability. With increasing concentration of SiO2, the temperature for 10-yr data retention increased to 131°C. In addition, the SiO2 -doped Sb2 Te based device remains a fast operation speed (10 ns). XRD and TEM results suggest the incorporation of SiO2 suppress the crystallization of Sb2 Te and then smaller grain size obtained, which benefits to the operation speed and power consumption.